Analysis of the Construct Validity and Internal Consistency of the State-Trait Anxiety Inventory (STAI) State-Anxiety (S-Anxiety) Scale for Pregnant Women during Labor - Delgado, Alexandre Magno; Freire, Alessandra da Boaviagem; Wanderley, Elaine Lima Silva; Lemos, Andrea (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Purpose To analyze the internal consistency and the construct validity of the State-Trait Anxiety Inventory (STAI) State-Anxiety (S-Anxiety) scale for pregnant women during labor.Method A study of measurement property including 150 pregnant women aged between 15 and 45 years old, during the first period of labor and with term pregnancies. The questionnaire used was the STAI S-Anxiety scale. In order to assess the internal consistency, Cronbach's α was calculated through an exploratory factor analysis. The correlation between the factors was calculated using the Pearson coefficient. The state of significance used for this analysis was 0.05.Results The STAI S-Anxiety scale used in the context of labor showed two factors represented as the absence (factor 1) and the presence of anxiety (factor 2); item 4 (“I regret it”) did not show a representative value. Both factors showed high indications of Cronbach's α, varying from 0.830 for factor 1, and 0.723 for factor 2. In the results of the Pearson coefficient between the two factors, a significant but weak correlation was observed (r = -0.188; p = 0.021).Conclusion The STAI S-Anxiety scale used in pregnant women during labor presented appropriate values of internal consistency; however, item 3 did not show a significant factorial value. Therefore, this questionnaire must be applied cautiously and carefully without the use of the item 4 in the clinical practice and in researches about labor.
Keywords: labor; anxiety; pain; factor analysis